Using an inerter-based suspension to improve both passenger comfort and track wear in railway vehicles. Issue 3 (3rd March 2020) - Lewis, T. D.; Jiang, J. Z.; Neild, S. A.; Gong, C.; Iwnicki, S. D.
ABSTRACT: There is an increasing desire in the railway industry to improve the longevity of wheels and rails without reducing performance in other ways (e.g. worsening passenger comfort). One way of reducing track and wheel wear is to reduce the primary yaw stiffness, significantly diminishing the costs associated with maintenance and emergency repairs, resulting however in reduced passenger comfort and high-speed stability. This paper, using a two-axle railway vehicle case study, demonstrates the potential of using passive, inerter-based suspensions to concurrently improve ride comfort and reduce track wear. The industrial parameter T γ is used to quantify the frictional energy lost at the contact patch under curving conditions, and the lateral RMS carbody acceleration is used to quantify passenger comfort under straight running conditions, with lateral track disturbances taken from real track data. Optimisation results conclude that, with the default yaw stiffness value, compared with the default spring-damper configuration in the primary lateral suspension, employing beneficial inerter-based configurations can improve passenger comfort by up to 43%. If the yaw stiffness is reduced such that the track wear is improved, similar improvements in passenger comfort can still be achieved with lateral inerter-based suspensions; for example, an improvement of 33% can still be achieved with a 50% reduction in yaw stiffness. Furthermore, when an inerter-based lateral suspension is used together with a Hall-Bush longitudinal suspension, the passenger comfort rises to 40%, which relates to a 25% improvement when compared with a non-inerter lateral plus Hall-Bush longitudinal setup.